Room-temperature super-extraction system (RTSES) optimizes the anxiolytic- and antidepressant-like behavioural effects of traditional Xiao-Yao-San in mice - Yin Shih-Hsi; Wang Ching-Cheng; Cheng Tain-Junn; Chang Chia-Yu; Lin Kao-Chang; Kan Wei-Chih; Wang Hsien-Yi; Kao Wenny; Kuo Yen-Liang; Chen Jian-Chyi; Li Shun-Lai; Cheng Chia-Hui; et al. (BMC, 2012)
Abstract Background Xiao-Yao-San (XYS) is a Chinese medicinal formula for treating anxiety and depression. This study aims to evaluate the use of a room-temperature super-extraction system (RTSES) to extract the major active components of XYS and enhance their psycho-pharmacological effects. Methods The neuroprotective roles of XYS/RTSES against reserpine-derived neurotoxicity were evaluated using a glial cell injury system (in vitro) and a depression-like C57BL/6 J mouse model (in vivo). The anxiolytic-behavioural effects were measured by the elevated plus-maze (EPM) test and the antidepressant effects were evaluated by the forced swimming test (FST) and tail suspension test (TST). Glucose tolerance and insulin resistance were assayed by ELISA. The expression of 5-HT1A receptors in the prefrontal cortex was examined by western blotting. Results XYS/RTSES (300 μg/mL) diminished reserpine-induced glial cell death more effectively than either XYS (300 μg/mL) or fluoxetine (30 μM) at 24 h (P = 0.0481 and P = 0.054, respectively). Oral administration of XYS/RTSES (500 mg/kg/day) for 4 consecutive weeks significantly elevated the ratios of entries (open arms/closed arms; P = 0.0177) and shuttle activity (P = 0.00149) on the EPM test, and reduced the immobility time by 90% on the TST (P = 0.00000538) and FST (P = 0.0000053839). XYS/RTSES also improved the regulation of blood glucose (P = 0.0305) and increased the insulin sensitivity (P = 0.0093). The Western blot results indicated that the activation of cerebral 5-HT1A receptors may be involved in the mechanisms of XYS/RTSES actions. Conclusion The RTSES could provide a novel method for extracting effective anxiolytic- and antidepressant-like substances. XYS/RTSES improved the regulation of blood glucose and increased the insulin sensitivity in reserpine-induced anxiety and depression. Neuroprotection of glial cells and activation of cerebral 5-HT1A receptors were also involved.